Effectiveness and safety of self-pulling and latter transection reconstruction in totally laparoscopic right hemicolectomy - Yang, Fuyu; He, Fan; Tang, Chenglin; Chen, Defei; Xiong, Junjie; Zou, Yu; Woraikat, Saed; Qian, Kun; Li, Hui (Frontiers in Oncology, 2024)
Background: Laparoscopic right hemicolectomy is a standard treatment modality for right colon cancer. However, performing intracorporeal anastomosis (IA) for totally laparoscopic right hemicolectomy (TLRH) remains a challenge for some surgeons. To simplify IA in TLRH we used self-pulling and latter transection (SPLT) reconstruction in TLRH, and compared this procedure with overlap IA and laparoscopy-assisted right hemicolectomy (LARH) in order to evaluate its safety and effectiveness.Methods: Patients with right colon cancer who underwent SPLT-TLRH, TLRH with overlap IA or LARH between July 2019 and June 2023 were evaluated retrospectively. Basic information, oncological features, perioperative outcomes, and postoperative complications were compared between groups.In total, 188 patients with right colon cancer that underwent SPLT-TLRH (n = 60), TLRH(n=21) or LARH (n = 107) were included in the study. No patient required conversion to open surgery. The operation time in SPLT-TLRH group was significantly shorter than that in TLRH group (P＜0.05). Compared with LARH group, SPLT-TLRH group had significantly longer distal margins, shorter skin incisions (P < 0.001), time to first flatus, time to first defecation, and postoperative hospital stays (P＜0.05).We introduced SPLT to TLRH. The SPLT-TLRH group demonstrated better shortterm outcomes. Therefore, we believe that SPLT reconstruction is effective and safe in TLRH for right colon cancer, and can simplify reconstruction.